Essays on migration and risk aversion - Umblijs, Janis (Trinity College (Dublin, Ireland). Department of Economics, 2013)
In this thesis I develop the theoretical and empirical literature linking risk aversion and migration. The thesis consists of three chapters exploring this theme from a variety of perspectives. The first chapter looks at the relationship between risk aversion and migration flows; the second investigates how risk preferences influence remittance behaviour; and the third tests the relationship between risk aversion and entrepreneurship among migrants.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.